2021
DOI: 10.1111/jcpe.13416
|View full text |Cite
|
Sign up to set email alerts
|

SLPI in periodontal Ligament is not sleepy during biophysical force‐induced tooth movement

Abstract: Aim:We aimed to identify a key molecule that maintains periodontal tissue homeostasis during biophysical force-induced tooth movement (BTM) by orchestrating alveolar bone (AB) remodelling. Materials and Methods: Differential display-PCR was performed to identify key molecules for BTM in rats. To investigate the localization and expression of the identified molecules, immunofluorescence, real-time RT-PCR and Western blotting were performed in rats and human periodontal ligament (PDL) cells. Functional test and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…A balanced cross-talk between these cells is mandatory for maintaining periodontal homeostasis (Liu et al, 2017;Aveic et al, 2021). Accordingly, PDL-derived biological molecules in BFTM have been widely investigated (Krishnan & Davidovitc, 2009;Lee et al, 2015Lee et al, , 2021Yang et al, 2015). Nevertheless, the homeostatic regulation of compression-induced AB resorption and tension-induced formation during BFTM, which occur concurrently and synchronized, has yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A balanced cross-talk between these cells is mandatory for maintaining periodontal homeostasis (Liu et al, 2017;Aveic et al, 2021). Accordingly, PDL-derived biological molecules in BFTM have been widely investigated (Krishnan & Davidovitc, 2009;Lee et al, 2015Lee et al, , 2021Yang et al, 2015). Nevertheless, the homeostatic regulation of compression-induced AB resorption and tension-induced formation during BFTM, which occur concurrently and synchronized, has yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…The factor that directly triggers BF‐induced TM (BFTM) is the transfiguration experienced by PDL cells and the extracellular matrix. This morphological modification causes the alteration of gene expression, subsequently inducing the release of cytokines from PDL cells (Meeran, 2013; Lee et al, 2021). Notably, the time‐dependent increase of BFTM while using orthodontic appliances is attenuated.…”
Section: Introductionmentioning
confidence: 99%
“…The process and pathway enrichment analysis showed that ossification (GO:0001503) and negative regulation of proteolysis (GO:0045861) were enriched at mesial and distal sides of the PDL. It has been well accepted that the cells in PDL maintain the adjacent alveolar bone by resorption and apposition of the bone matrix ( Jiang et al, 2016 ; Moon et al, 2019 ; Lee et al, 2021 ). The enrichment of the “negative regulation of proteolysis” indicated that antagonizing mechanisms against ECM degradation were enhanced in response to the mechanical loading.…”
Section: Discussionmentioning
confidence: 99%
“…LPS induces RANKL expression from osteoblasts and production of proinflammatory cytokines, such as TNF-α and IL-1, from macrophages and other cells ( 37 ). It has been reported that periodontal ligament cells also express numerous types of proinflammatory cytokines to regulate osteoclastogenesis by LPS ( 38 ). RANKL and TNF-α contribute to LPS-induced osteoclastogenesis and bone resorption ( 39 ).…”
Section: Discussionmentioning
confidence: 99%